Criticism of Contemporary Islamic Monetary Policy and Operations: Indonesia Case Study - Santoso, Muhammad Rifky (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bank Indonesia (BI) as the central bank in Indonesia has a role to maintain the stability of the rupiah (IDR) value. One of the BI’s activities is sharia monetary operations (OMS). The OMS relates to the absorption and injection of liquidity with Islamic banking as a participant. Therefore, it is necessary to see whether this OMS is under sharia principles. The OMS instruments analyzed are SBIS, SukBI, PasBI, SBSN, financing facilities, and FASBIS transactions. This article uses desk research and content analysis of relevant data and information. This article finds that SukBI transactions and SBSN transactions are fully under sharia principles. SBIS, PasBI, financing facility and FASBIS transactions are not fully following sharia principles because the contract (aqad) used is not under the substance of the transaction. It is recommended to change the contract (aqad) or adjust the substance of the transaction with the aqad being made